Oil water contact analysis and hydrocarbon saturation estimation based on well logging data - Setyowiyoto, Jarot; Samsuri, Ariffin (2006)
Oil water contact analysis, porosity calculation and hydrocarbon saturation estimation is very important stage in reservoir characterization and hydrocarbon reserve estimation. Well logging data studied comprises of gamma ray log, formation density and compensated neutron logs, and electric logs. As a result, the lithology of the well is interbedded between sandstone and claystone. The hydrocarbon is trapped in ten porous zones that have the reservoir thickness vary between 11 - 90 feet. Oil water contact occured at the 2229 feet depth characterized by the rapid change of resistivity, and underneath became oil depletion zone. The highest hydrocarbon saturation encountered in the zone no .1 that is 85.7 % with 19 feet thick and formation temperature is 157.4 deg F. Porosity is affected by clay volume and their density, whereas the hydrocarbon saturation is strongly influenced by porosity and their value of resistivity log.